MODELING DNA DAMAGE BY PHOTONS AND LIGHT IONS OVER ENERGY RANGES USED IN MEDICAL APPLICATIONS. Issue 1 (11th December 2018) - Friedland, W; Kundrát, P; Schmitt, E; Becker, J; Li, W
Abstract: Comprehensive track structure-based simulations of DNA damage induced in human cells by photons (5 keV–1.3 MeV) and light ions (0.25–512 MeV/u) were performed with PARTRAC. DNA strand breaks, double-strand breaks and their clustering were scored. Effective LET values were established for photons that provide LET-dependent damage yields in agreement with the data for ions. The resulting database captures the variations of biological effectiveness with radiation quality. In particular, it can help compare the effectiveness of conventional radiotherapy using photon beams with techniques relying on proton or ion beams.